Comprehensive Care for Patients with Low Back Pain in The Third Trimester of Pregnancy - Rena Oki Alestari; Ivana Devitasari; Evy Kasanova; Lidia Widia (KHD Production, 2025)
Discomfort during the third trimester of pregnancy, such as back pain, is a common complaint experienced by pregnant women due to physiological changes in the body. This study aims to provide comprehensive midwifery care to patients with complaints of low back pain. This research is a case study conducted at the Pasir Putih Health Center from April to June 2024. The subject of the study is Mrs. AS, who is 34 weeks pregnant with a single live intrauterine fetus in cephalic presentation. Instruments include midwifery care formats, observation sheets, screening forms, and partographs—data collection techniques employed both primary and secondary approaches. The results showed that the comprehensive midwifery care proceeded smoothly, with all examination results within normal limits. No discrepancies were found between facts and theories, as the midwifery care was carried out according to established standards. Documentation of the examination results was recorded using the Varney 7-step management framework and SOAP format. In conclusion, the comprehensive midwifery care provided to the patient proceeded successfully without any complications or pathological conditions detected. This demonstrates that the application of standardized midwifery care can optimally support maternal health during the third trimester of pregnancy